SOCIAL AND ECONOMIC VULNERABILITY FOR THE 2007 FLOOD EVENT - , Ali Achmadi; , Dr. rer. nat. Muh Aris Marfai, S.Si., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The unit analysis is RT level as the mapping unit on this research. The flood character is different related to the location with the river. The sampling method is conducted using stratified location related to dike, protected by dike and unprotected by dike of settlement area. The mapping unit on RT level also gives differenced pattern of social and economic condition. The sampling method is also built on stratified of housing settlement, the old developed and new developed settlement. This research is limited on residential area. The non-settlement area, such as agricultural and industrial use, is analyzed using the individual person who works on it. There are two main vulnerabilities that used to predict the community vulnerability. Those are social and economy vulnerability. There are four character of 2007 flood event that decided by community. Those are flood depth, duration, water velocity and flood rising. On Kadokan, the most impact flood character is flood rising, while on Telukan it is the less impact flood character. Mostly on Kadokan is experienced by moderate to strong impact, while Telukan mostly dominated by low to moderate impact. There are five indicators on social vulnerability, gender, health habit on using drinking water, age range distribution, housing condition and disability people. On economy vulnerability, they are two indicators, occupation type that affected by flood event and local economic base. The social vulnerability value of old developed settlement is higher than new developed settlement. The protected by dike and old settlement sample type is the most vulnerable than settlement that unprotected by dike. The highest value of economic vulnerabilityis found in old developed settlement that unprotected by dike. The relation of social and economic vulnerability with the 2007 flood impacts use to find the suggested location on flood management priority. It is consist of the 2007 flood impactâs relation on social and economy vulnerability. Mostly in Kadokan, especially which is unprotected by dike is classified on very strongly priority. The extremely less priority is found in Telukan that consists of new developed settlement.